2014
DOI: 10.1111/anae.12593
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inhalational anaesthetics in experimental allergic asthma

Abstract: SummaryWe evaluated whether isoflurane, halothane and sevoflurane attenuate the inflammatory response and improve lung morphofunction in experimental asthma. Fifty-six BALB/c mice were sensitised and challenged with ovalbumin and anaesthetised with isoflurane, halothane, sevoflurane or pentobarbital sodium for one hour. Lung mechanics and histology were evaluated. Gene expression of pro-inflammatory (tumour necrosis factor-a), pro-fibrogenic (transforming growth factor-b) and pro-angiogenic (vascular endotheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 47 publications
0
16
0
4
Order By: Relevance
“…In addition, sodium THIO does not affect baseline airway tone, 26 lung mechanics, or histology. 16,26 A protective ventilatory strategy was used to discard possible biological effects associated with mechanical ventilation, which may yield confounding results. Infusion rates of sodium THIO, PRO, and DEX were based on experimental studies that reported negligible effects of these agents on hemodynamic variables in rats 6,14,16 when given for 1 hour.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…In addition, sodium THIO does not affect baseline airway tone, 26 lung mechanics, or histology. 16,26 A protective ventilatory strategy was used to discard possible biological effects associated with mechanical ventilation, which may yield confounding results. Infusion rates of sodium THIO, PRO, and DEX were based on experimental studies that reported negligible effects of these agents on hemodynamic variables in rats 6,14,16 when given for 1 hour.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…In their letter about using the infant Airtraq â for placing a adult gumelastic bougie [1], Smith and Maloney stated that the smallest available Airtraq laryngoscope permitted a good laryngeal view in an adult manikin, its narrow guiding channel allowing introduction of an adult gum-elastic bougie into the glottis for subsequent insertion of a normal adult tube. We are interested whether the authors have used this method in adult patients.…”
Section: Infant Airtraq â For Adult Bougie Placementmentioning
confidence: 99%
“…In their 'morphofunctional' model of induced allergic asthma, Burburan and colleagues report that inhalational anaesthetic agents, particularly sevoflurane, reduce inflammatory cytokine gene expression in the lungs of mice receiving intratracheal ovalbumin [1]. The authors list some limitations of their study, but we would like to add that volatile anaesthetic agents have major effects on pulmonary blood flow, which may be of relevance in the asthmatic process.…”
mentioning
confidence: 99%
“…They are postulated to work via direct relaxation of bronchial smooth muscle, inhibition of the release of inflammatory mediators, β-adrenergic receptor stimulation, reduction of vagal tone and vagal-mediated reflexes and antagonism of the effects of histamine and methacholine 4 5. Animal models also suggest sevoflurane functions through immune modulation to inhibit leukotriene-induced inflammation, downregulating tumour necrosis factor-α, transforming growth factor-β and vascular endothelial growth factor, increasing the Nrf2 protective antioxidant response and dampening sirt-1, catalase and glutathione peroxidase expression 6–8…”
Section: Introductionmentioning
confidence: 99%